2020
DOI: 10.3390/catal10020154
|View full text |Cite
|
Sign up to set email alerts
|

The Fatty-Acid Hydratase Activity of the Most Common Probiotic Microorganisms

Abstract: In this work, we studied the biotechnological potential of thirteen probiotic microorganisms currently used to improve human health. We discovered that the majority of the investigated bacteria are able to catalyze the hydration reaction of the unsaturated fatty acids (UFAs). We evaluated their biocatalytic activity toward the three most common vegetable UFAs, namely oleic, linoleic, and linolenic acids. The whole-cell biotransformation experiments were performed using a fatty acid concentration of 3 g/L in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…However, some studies describe hydratase activity in yeast [27,31], and this fact has been questioned recently [32]. Our studies on the potential yeast-mediated hydration of oleic acid (1) confirmed also that Saccharomyces species do not possess hydratase activity [33,34]. Bacterial contaminants of commercial baker's yeast are responsible for the stereoselective conversion of oleic acid (1) into 10-hydroxystearic acid (2).…”
Section: Introductionsupporting
confidence: 61%
“…However, some studies describe hydratase activity in yeast [27,31], and this fact has been questioned recently [32]. Our studies on the potential yeast-mediated hydration of oleic acid (1) confirmed also that Saccharomyces species do not possess hydratase activity [33,34]. Bacterial contaminants of commercial baker's yeast are responsible for the stereoselective conversion of oleic acid (1) into 10-hydroxystearic acid (2).…”
Section: Introductionsupporting
confidence: 61%
“…These biochemical transformations were discovered in the early 1960s, during a study on the hydration of oleic acid (Figure 1) using a Pseudomonas strain [6,7]. Afterwards, a number of other microorganisms proved to be able to perform this transformation [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] but the enzymes responsible for the hydration step (oleate hydratases) have been characterized only recently [24]. Oleate hydratases (OLH, EC 4.2.1.53) convert oleic acid (OA) into (R)-10-hydroxystearic acid (10-HSA) [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], a high value commercial molecule due to its potential application as surfactant, lubricant, additive in cosmetics industries, and as a starting material in polymer and flavor chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Being involved in a research project aimed at the valorization of the vegetable oils waste, we studied the biocatalytic hydration of the latter fatty acids using both microbial transformations [21][22][23] and isolated hydratase [26]. In this context, we demonstrated the versatility of the probiotic bacteria Lactobacillus rhamnosus ATCC 53103 [22], which is able to hydrate oleic, linoleic, and linolenic acid affording (R)-10-hydroxystearic acid, (S)-(12Z)-10-hydroxy-octadecenoic acid, and (S)-(12Z,15Z)-10-hydroxy-octadecadienoic acid, respectively, in very high enantiomeric purity (ee > 95%), without the formation of other regioisomers or polyhydroxylated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oleate hydratase (Ohy) belongs to the first group acting on isolated double bonds in fatty acids e.g. oleic acid to produce 10-hydroxystearic acid (Scheme 1) (Demming et al 2018;Engleder and Pichler 2018;Serra et al 2020). Up until now, all characterised Ohys are FAD-dependent.…”
Section: Introductionmentioning
confidence: 99%